Analisis Energi dan Eksergi Sistem Rankine Organik Dan Sistem Refrigerasi Kompresi Uap Yang Terintegrasi - Ferdyson, Ferdyson; Kiono, Berkah Fajar Tamtomo; Sutaryo, Sutaryo (BRILIANT: Jurnal Riset dan Konseptual, 2025)
The utilization of waste heat is currently a growing trend that has gained global attention due to its contribution to new and renewable energy. Low-temperature waste heat can be used in an Organic Rankine Cycle (ORC) for cooling purposes. This study aims to utilize waste heat from a ceramic cooling machine by integrating the ORC with the Vapor Compression Refrigeration (VCR) cycle to obtain the optimal refrigerant and system performance. Thermodynamic analysis methods based on energy and exergy analysis were conducted using refrigerants R1234ze(E), R152a, RC318, R236fa, RE245cb2, R600a, R236ea, and R245fa as working fluids under operational conditions, varying the evaporator, condenser, and boiler temperatures, as well as the efficiency of the compressor and turbine. Based on the thermodynamic analysis (energy and exergy), R152a was selected as the best working fluid for this application. The coefficient of performance (COP) of the integrated ORC-VCR system was 0.6122, resulting in a cooling capacity of 16.26 kW and an exergy efficiency of 0.5017.